Intellectual property rights related to the genetically modified glyphosate tolerant soybeans in Brazil - Rodrigues,Roberta L (2011)
The present work analyzes the different modalities of protection of the intellectual creations in the biotechnology agricultural field. Regarding the Brazilian legislations related to the theme (the Industrial Property Law - no. 9. 279/96 and the Plant Variety Protection Law - no. 9. 456/97), and based in the international treaties signed by Brazil, the present work points to the inclusions of each of them, as well as to their interfaces using as reference the case study of glyphosate tolerant genetically modified soybean. For this case study, Monsanto's pipelines patents were searched and used to analyze the limits of patent protection in respect to others related to the Intellectual Property (IP) laws. Thus, it was possible to elucidate the complex scenario of the Intellectual Property of the glyphosate tolerant soybeans, since for the farmer it is hard to correlate the royalties payment with the IP enterprise's rights